UI/UX Development of a Boarding House Reservation Application: A Design Thinking Approach in Surabaya - Azizatul Fara Dibah; Abdul Rezha Efrat Najaf; Prasasti Karunia Farista Ananto (bit-Tech, 2025)
Fragmented, inconsistent, and frequently outdated information about boarding-house availability, facilities, and pricing remains a persistent usability problem in existing digital platforms. Current UI/UX and reservation-system research has not sufficiently addressed these issues within the specific context of urban rental ecosystems, creating gap in designing solutions that respond to the needs of both tenants and property owners. This study addresses that gap by developing and evaluating a user-centered interface for a boarding-house reservation application using the five-stage Design Thinking framework: empathize, define, ideate, prototype, and test. Insights were gathered from 30 participants representing owners, tenants, and administrators in Surabaya, forming the basis for personas, information architecture, user flows, and low- to high-fidelity prototypes designed in Figma. Usability and interface quality were examined through task-based testing, the System Usability Scale (SUS), and Nielsen’s heuristic evaluation to integrate both user perception and normative usability standards. Initial testing produced SUS scores of 74.5 (owners), 76.5 (tenants), and 66 (administrators), indicating acceptable but improvable usability and several interface issues. Iterative refinement led to marked enhancements, with second-round SUS scores of 90, 87, and 89, accompanied by high learnability (96–97%), strong memorability (95–96%), and low error rates (0.0306–0.0800). A minor efficiency decrease was attributed to unstable network conditions rather than design flaws. Overall, the findings demonstrate that structured, iterative UI/UX development supported by heuristic auditing effectively resolves core information and interaction challenges in boarding-house reservation systems. The final prototype demonstrates high usability and provides a replicable design rationale for future implementation and scaling.